A green hydrogen economy for a renewable energy society. (September 2021) - Oliveira, Alexandra M; Beswick, Rebecca R; Yan, Yushan
Highlights: Green hydrogen is uniquely equipped to decarbonize sectors which do not have green alternatives. A 'hydrogen economy' is an essential secondary energy economy to realizing a majority renewable energy society. Early implementation of green hydrogen will be in the current chemical synthesis market. Hydrogen will penetrate the transportation and buildings and heating sectors in the midterm transition toward 100% renewables. Hydrogen will be a necessary seasonal storage technology in the long term. Abstract : A hydrogen economy has long been promoted as a ground-breaking aspect of a low-carbon future. However, there is little consensus on what this future entails, with some overly concerned about lack of demand and others disregarding hydrogen's limitations. Here, we fill the need for a comprehensive definition of the 'hydrogen economy' and illustrate a vision in which hydrogen will primarily be used for decarbonization where no alternative exists. We propose a three-phase implementation plan for hydrogen into the industrial sector as a chemical feedstock, the transportation sector for long-range, heavy-duty vehicles, the buildings sector for heat, and the power sector for seasonal storage. We find that hydrogen will not be the largest energy economy, but with a projected need of 2.3 Gt H2 annually, it can decarbonize around 18% of energy-related sectors. In the long-term, hydrogen can complement renewable electricity and be the keystone to a 100% renewable future.